Memory-like innate lymphoid cells in the pathogenesis of asthma - Ham, Jongho; Lim, MinYeong; Kim, Dongmo; Kim, Hye Young (Frontiers in Immunology, 2022)
Innate lymphoid cells (ILCs) are recently discovered innate immune cells that reside and self-renew in mucosal tissues and serve as the first line of defense against various external insults. They include natural killer (NK) cells, ILC1s, ILC2s, ILC3s, and lymphoid tissue inducer cells. The development and functions of ILC1–3 reflect those of their adaptive immunity TH1, TH2, and TH17 T-cell counterparts. Asthma is a heterogeneous disease caused by repeated exposure to specific allergens or host/environmental factors (e.g., obesity) that stimulate pathogenic pulmonary immune cells, including ILCs. Memory used to be a hallmark of adaptive immune cells until recent studies of monocytes, macrophages, and NK cells showed that innate immune cells can also exhibit greater responses to re-stimulation and that these more responsive cells can be long-lived. Here, we discuss the biology of ILCs, their roles in asthma pathogenesis, and the evidence supporting ILC memory. We also show evidence suggesting memory ILCs could help drive the phenotypic heterogeneity in asthma. Thus, further research on memory ILCs may be fruitful in terms of developing new therapies for asthma.